West Nile Virus Outbreak in Houston and Harris County, Texas, USA, 2014 - Martinez, Diana (Emerg Infect Dis, 2017)
Since 2002, West Nile virus (WNV) has been detected every year in Houston and the surrounding Harris County, Texas. In 2014, the largest WNV outbreak to date occurred, comprising 139 cases and causing 2 deaths. Additionally, 1,286 WNV-positive mosquito pools were confirmed, the most reported in a single mosquito season.